Basics of Hebrew discourse : a guide to working with biblical Hebrew prose and poetry - Patton, Matthew H.; Putnam, Frederic C.; Van Pelt, Miles V., 1969- (Grand Rapids Zondervan Academic, 2019)
"Basics of Hebrew Discourse introduces intermediate Hebrew students to the principles and exegetical benefits of discourse analysis (text linguistics) when applied to biblical Hebrew prose and poetry. Where standard Hebrew reference grammars have traditionally worked to describe the relationships between words and phrases within discrete clauses (micro-syntax), discourse analysis works to describe the relationships that exist between clauses and texts (macro-syntax). This resource fills a needed gap for intermediate Hebrew students and gives them the tools to work with Hebrew syntax on the macro-level, making clear the relationships between clauses, paragraphs, and larger units of text in Hebrew prose and poetry. Professors and pastors working with Hebrew will also find this one-of-a-kind resource highly valuable."
Includes bibliographical references and indexes.
Keywords: Bible. -- Language, style; Bible; Discourse analysis; Hebrew poetry, Biblical; Hebrew language -- Discourse analysis; Discourse analysis; Hebrew language -- Discourse analysis; Hebrew poetry, Biblical